2019
DOI: 10.3390/ani9060290
|View full text |Cite
|
Sign up to set email alerts
|

Equine Activities Influence Horses’ Responses to Different Stimuli: Could This Have an Impact on Equine Welfare?

Abstract: The learning and cognitive challenges that horses may face differ according to the activities in which they are involved. The aim of this investigation was to study the influence of equine activities on the behavioral responses and autonomic nervous system (ANS) activity of adult horses. Forty-one horses were divided into four groups: dressage (9), jumping (10), eventing (13) and equine-assisted activity/therapy (9). A test was created to compare the horses’ behavioral and physiological responses to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The aim of this study was to find suitable ways to evaluate puppies at an early stage for the presence of fear, which is the reason for a significant number of failures in guide dog training [ 32 ]. The items used to construct this test have been independently validated in the literature [ 20 , 31 , 42 , 43 , 44 ]. The test confronts the animals with three categories of stimuli: sound and visual stimuli (SVS), body sensitivity (BS), and an unknown person (UP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to find suitable ways to evaluate puppies at an early stage for the presence of fear, which is the reason for a significant number of failures in guide dog training [ 32 ]. The items used to construct this test have been independently validated in the literature [ 20 , 31 , 42 , 43 , 44 ]. The test confronts the animals with three categories of stimuli: sound and visual stimuli (SVS), body sensitivity (BS), and an unknown person (UP).…”
Section: Discussionmentioning
confidence: 99%
“…This test is an evaluation procedure generally used by the FGF to evaluate dogs at one year of age. It was developed by members of the foundation specializing in canine behavior and by a veterinary behaviorist, adapted from some other procedures used by previously published tests in dogs or other species [ 20 , 31 , 42 , 43 , 44 ]. Due to the young age of the dogs, some items from the original evaluation procedure were removed to avoid overloading them emotionally.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that gate staff responded by using an "artificial aid", such as whipping over 40% of the time, which explains why TBI-4 made the downward comparison in relation to Image 3, stating "no one has a stock whip on him, no one is hitting him" (Section 4.2.2). Moreover, it can be suggested that many of the emotional and behavioural responses of the thoroughbreds in the images may, in fact, be learned or shaped by the human factor and the particular activity of racing as such [24]. The kind of relationship humans have with the horse shape the nature of the handling and training practices, and vice versa, the handling and training practices shape the nature of the horse-human relationship.…”
Section: The Horse-human Relationship As An Aspect Of a Holistic Notimentioning
confidence: 99%
“…Animal advocacy informants in the same study additionally identified routine training and husbandry practices, human-horse interactions and the “everyday life of horses” as “where the real welfare issues are” in thoroughbred racing [ 3 ]. These are issues discussed in the general equine welfare literature and include topics such as housing [ 4 , 5 , 6 , 7 ], feeding [ 8 , 9 ], equine behaviour [ 10 ], equine emotions [ 11 ], equine welfare assessment [ 12 , 13 ], the application of equipment [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], equine learning and training [ 22 , 23 ], the impact of equine activities on the horse [ 24 ], human handling during various forms of human-horse interactions [ 25 , 26 ], impacts of riding on behaviour and welfare [ 27 , 28 , 29 , 30 ], horse-human relationships [ 31 , 32 , 33 , 34 ] and people’s ability and inability to recognise behavioural signs of equine distress and pain [ 35 , 36 , 37 , 38 ]. A theme that unites these issues and that allows one to make assessments as to the welfare impact is naturalness, i.e., what is natural for the horse and what is in the horse’s nature in relation to their species-specific, as well as individual, physiological; emotional; cognitive; social and behavioural characteristics, abilities and boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the utility value of horses, it should be emphasised that a possibility of starting an exploratory activity is associated with a reward, so it can be used as reinforcement in the conditioning of instrumental responses [ 8 ]. Horses’ urge to explore correlates with behavioural and physiological responses to stimuli, which gives more information about the process of habituating or desensitizing horses to disturbing stimuli [ 27 ]. Due to various behavioural and physiological responses, the reactivity and emotional responses are different in horses taking part in different riding events.…”
Section: Introductionmentioning
confidence: 99%